Fire - Cashore, Kristin (New York : Firebird, 2011)
In a kingdom called the Dells, Fire is the last human-shaped monster, with unimaginable beauty and the ability to control the minds of those around her, but even with these gifts she cannot escape the strife that overcomes her world.
Originally published: New York : Dial Books, c2009.
Features a teaser for the sequel to Graceling and the companion to Fire-- Bitterblue.
Keywords: Magic -- Juvenile fiction; Extrasensory perception -- Juvenile fiction; Imaginary wars and battles -- Juvenile fiction; Kings and rulers -- Juvenile fiction; Brainwashing -- Juvenile fiction; Monsters -- Juvenile fiction; Courage -- Juvenile fiction; Good and evil -- Juvenile fiction; Fantasy fiction; Young adult fiction; Fantasy fiction